A single-phase high-entropy rare earth-based ceramic catalyst containing Fe or In, preparation method thereof and application thereof

By introducing hydrothermal synthesis method of Fe or In and five rare earth elements into high-entropy ceramic materials, the problems of complexity and performance limitations of the existing high-entropy ceramic materials synthesis system are solved, and the preparation of single-phase high-entropy phosphate and excellent catalytic performance are achieved.

CN116553508BActive Publication Date: 2025-04-25NANCHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310493910.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-05
Publication Date
2025-04-25
Estimated Expiration
2043-05-05

AI Technical Summary

Technical Problem

The synthesis system of existing high-entropy ceramic materials is complex, the equipment and operating conditions are harsh, and the composition of metal elements is limited, resulting in the performance similar to that of single-component materials and the special application functions predicted by theory are not realized.

Method used

Using an easy-to-operate, green and mild hydrothermal synthesis system, the transition metal element Fe or In which has a large difference in properties from rare earth elements is introduced, combined with five rare earth elements, and a single-phase high-entropy 6-member metal phosphate ceramic material is obtained through hydrothermal synthesis and heat treatment.

Benefits of technology

It is achieved by forming a single-phase high-entropy phosphate with the transition metal elements Fe or In with a large difference in properties, which significantly improves the catalytic performance, and the sulfoxide yield can reach more than 91%, enriching the lineage and preparation system of high-entropy ceramic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116553508B_ABST
    Figure CN116553508B_ABST
Patent Text Reader

Abstract

The invention discloses a single-phase high-entropy rare earth-based ceramic catalyst containing Fe or In, a preparation method and application thereof, and belongs to the field of new chemical materials. Among a series of transition metal elements tried, synthesis screening shows that only Fe(NO3)3 or In(NO3)3 and five rare earth nitrates (RE(NO3)3, RE=La, Ce, Nd, Sm, Gd) are mixed evenly in an aqueous solution, subjected to a hydrothermal synthesis reaction, and then roasted to obtain a rare earth-based ceramic material with a molar ratio of six metal elements close to each other and characterized by a single-phase high-entropy six-element metal phosphate, which is used as a catalyst for the reaction of preparing sulfoxide products by oxidation of anisole, and has excellent performance. Compared with the reported methods, the system of the invention can combine rare earths with a large span of metal element properties with transition metal elements Fe or In to prepare single-phase high-entropy phosphates through a mild, green, simple and easy-to-operate process, enriching the spectrum of high-entropy compounds, and providing a model for developing new uses of such materials, especially catalytic applications, and has a significant reference and promotion and application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method for preparing a single-phase high-entropy rare-earth-based ceramic catalyst containing Fe or In, belongs to the field of new chemical materials, and aims to provide a synthesis and catalytic application method for preparing a single-phase high-entropy rare-earth-based phosphate ceramic material by combining transition metal elements with rare earth elements. Background Art

[0002] High entropy materials refer to alloys or non-alloy single-phase compounds that are complex in composition, locally microscopically disordered, and overall macroscopically ordered, containing more than five metal elements with similar metal molar compositions, based on the entropy increase stabilization effect caused by the increase in the number of elements to more than five. The related non-alloy single-phase compounds are collectively referred to as high-entropy ceramic materials. Compared with conventional materials, these materials have special intrinsic properties such as microscopic lattice distortion, element hybridization, and metastable crystal field. They are considered to be a new type of inorganic material with great application potential, which has triggered a wave of research and application development in academia and industry.

[0003] Among the reported high-entropy ceramic materials, the synthesis and application research of high-entropy phosphates is still in its infancy, with few references, which limits the understanding and application of this type of materials. There are also many gaps and deficiencies. They mainly include: (1) The synthesis system method is relatively complex, and the equipment and operating conditions are harsh. For example, the common high-voltage arc and high-temperature vapor deposition methods are not suitable for large-scale synthesis; (2) The metal element composition of high-entropy compounds is limited to the same group or period elements in the periodic table, and the compound spectrum is relatively limited; (3) Due to the similar elemental properties of the synthesized materials, the actual performance is similar to that of single-component materials, and some special application functions predicted by theory have not yet been realized. In response to these prominent problems and shortcomings, we introduced one of the transition metal elements Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, In, etc., which has very different properties from rare earth elements but significant thermal catalytic properties, on the basis of synthesizing 5-membered rare earth-based high-entropy phosphates. Using an easy-to-operate, green and mild hydrothermal synthesis system, we attempted to synthesize and thermally catalytically apply single-phase high-entropy 6-membered metal phosphate ceramic materials. We found that among these transition metal elements, only Fe or In can be reacted with the five rare earths to form target structure high-entropy ceramic materials through hydrothermal synthesis and heat treatment. At the same time, the oxidation of anisole to produce sulfoxide compounds clarified that the synthesized single-phase high-entropy 6-membered rare earth-based phosphates containing Fe or In have excellent catalytic properties compared with hybrids formed by other transition metal elements. This proves that obtaining such single-phase high-entropy phosphates with a large span of properties and a large number of metal elements has specific requirements on the type and composition of metal elements, and the formation of a single-phase high-entropy structure is crucial to highlighting the application performance of such materials. Thus, a preparation method for combining five rare earths with Fe or In into a single-phase high-entropy six-element metal phosphate was developed through a mild, green, simple and easy-to-operate hydrothermal synthesis system, and it was verified that this type of high-entropy ceramic has excellent catalytic performance. High-entropy ceramic materials with similar composition and structure and their thermal catalytic performance have not been reported, indicating that the samples obtained by this method not only enrich the spectrum and preparation system of high-entropy ceramic materials, but also reveal or realize the new application function of high-entropy ceramic materials as thermal catalysts. In addition, the samples obtained by this method are screened on the basis of many failed experiments. For example, only Fe and In among the multiple transition metals tested have achieved the successful synthesis of the target structure samples, which further demonstrates the particularity and originality of this method, and hereby applies for patent protection. Summary of the invention

[0004] In the process of attempting to combine one of the metal elements Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, In with five lanthanide rare earth elements (La, Ce, Nd, Sm, Gd) with phosphorus-containing ligands, a method for preparing a single-phase high-entropy rare earth-based phosphate ceramic catalyst containing Fe or In was invented. Specifically, iron nitrate (Fe(NO3)3) or indium nitrate (In(NO3)3) and five rare earth nitrates (RE(NO3)3, RE=La, Ce, Nd, Sm, Gd) are mixed in equal proportions and dissolved in water, and excess phosphorus-containing ligands are introduced. After hydrothermal synthesis and heat treatment, a single-phase high-entropy six-membered metal phosphate catalyst composed of Fe or In and five rare earth elements is obtained. The catalyst is used for the thermal catalytic reaction of anisyl thioether oxidation to produce sulfoxide compounds, and has excellent performance.

[0005] The present invention is achieved through the following technical solutions:

[0006] The first aspect of the present invention provides a method for preparing a single-phase high-entropy rare earth-based ceramic catalyst containing Fe or In. The method comprises the following steps: uniformly mixing ferric nitrate (Fe(NO3)3) or indium nitrate (In(NO3)3) with five rare earth nitrates (RE(NO3)3, RE=La, Ce, Nd, Sm, Gd) in an aqueous solution, adding an excess of a phosphorus-containing ligand to carry out a hydrothermal synthesis reaction, and calcining the obtained precursor complex to obtain a 6-membered metal phosphate ceramic material, which is used as a catalyst for the oxidation of anisole to prepare sulfoxide products.

[0007] The preparation method of the above-mentioned 6-membered metal phosphate catalyst specifically comprises the following steps:

[0008] (1) iron nitrate (Fe(NO3)3) or indium nitrate (In(NO3)3) and five kinds of rare earth nitrates are mixed in a molar ratio of La:Ce:Nd:Sm:Gd:M:P=0.16±0.04:0.16±0.04:0.16±0.04:0.16±0.04:0.16±0.04:0.16±0.04:1 (M=Fe or In) to prepare an aqueous solution, add an excess of phosphorus-containing ligand, stir at 500-700 r / min for 20-40 minutes, and then transfer to a hydrothermal reactor to react at 150-200°C for 20-30 hours;

[0009] (2) The precipitate obtained by centrifuging the reaction solution system is washed alternately four times with ethanol and deionized water, and then vacuum dried at 50-70° C. for 10-14 h to obtain a precursor.

[0010] (3) Calcine the precursor at 500-700° C. in air for 3-5 h to obtain a hexavalent metal phosphate catalyst.

[0011] An excess amount of phosphorus-containing ligand is added, wherein the phosphorus-containing ligand refers to phosphoric acid or phosphate including phosphate, monohydrogen phosphate and dihydrogen phosphate, and the excess amount means that the molar ratio of the phosphorus-containing ligand to the total amount of the metal element is controlled to be 1.1-1.5.

[0012] The obtained hexavalent metal phosphate catalyst has a phosphate molar composition of 1, and the molar compositions of Fe or In and five rare earth elements La, Ce, Nd, Sm, and Gd are all close to 0.16, with a floating range of 0.16±0.04; the formed phosphate is in a single crystalline phase.

[0013] The second aspect of the present invention provides a single-phase high-entropy rare earth-based ceramic material containing Fe or In prepared by the above method, which is a hexavalent metal phosphate in a single crystal phase.

[0014] The third aspect of the present invention provides an application of a single-phase high-entropy rare earth-based ceramic material containing Fe or In prepared by the above method, wherein the obtained 6-membered metal phosphate is used as a thermal catalyst for the thermal catalytic reaction of anisole oxidation to produce sulfoxide compounds, and has excellent performance.

[0015] Specifically, thioanisole is dissolved in an acetonitrile solution, the Fe or In-containing single-phase high-entropy rare earth-based ceramic material is added as a catalyst, and then a 30wt% H2O2 solution is added, the molar ratio of H2O2 to thioanisole is 1.5-2.5:1, and the mixture is heated to 50-70°C and reacted for 120-150 minutes to generate sulfoxide compounds, and the yield of the target product sulfoxide can reach more than 91%.

[0016] Technical effect of the present invention: Compared with the prior art, the preparation system of the present invention has relatively mild conditions, is easy to operate, and is suitable for large-scale preparation of samples; the more prominent effect is that it can realize the formation of 6-element single-phase high-entropy phosphates with rare earth elements with large property differences and transition metal elements Fe or In, and the obtained material has excellent catalytic performance. The synthesis and catalytic application research of high-entropy ceramic materials with similar composition and structure have not been reported in databases such as papers and patents, indicating that the samples obtained by this method not only enrich the spectrum and preparation system of high-entropy ceramic materials, but also reveal or realize the new application function of high-entropy ceramic materials as catalysts. In addition, the samples obtained by this method are screened on the basis of many failed experiments. For example, only Fe and In among the multiple transition metals tested have achieved the successful synthesis of target structure samples, which further demonstrates the particularity and originality of this method. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 X-ray diffraction (XRD) spectra of polyphosphates (LaCeNdSmGd)PO4, Cu-(LaCeNdSmGd)PO4, Al-(LaCeNdSmGd)PO4, Fe-(LaCeNdSmGd)PO4, and In-(LaCeNdSmGd)PO4;

[0018] Figure 2 This is a scanning electron microscope (SEM) image of Fe-(LaCeNdSmGd)PO4. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with the accompanying drawings.

[0020] Example 1: Fe-(LaCeNdSmGd)PO4 Catalyst

[0021] Dissolve 1 mmol of each of Fe(NO3)3·9H2O and five kinds of rare earth nitrates RE(NO3)3·6H2O (RE=La, Ce, Nd, Sm, Gd) in 30 mL of deionized water, then add 30 mL of 0.2 mol / l diammonium hydrogen phosphate aqueous solution to the above nitrate solution at a rate of 0.5 ml / min under stirring, transfer to a hydrothermal reactor after stirring at 600 r / min for 30 minutes, and perform hydrothermal reaction at 180°C for 24 hours. After the reaction, separate the precipitate by centrifugation, wash it alternately with ethanol and deionized water four times, and vacuum dry it at 60°C for 12 hours to obtain a precursor; the precursor is calcined at 600°C in air for 4 hours to obtain a Fe-(LaCeNdSmGd)PO4 catalyst sample. As shown in Table 1, the molar ratio of each element in the sample is obtained by ICP-OES analysis: Fe: La: Ce: Nd: Sm: Gd: P = 0.14: 0.14: 0.18: 0.20: 0.16: 0.15: 1; and the XRD spectrum of the sample shows Figure 1 Compared with the standard rare earth phosphate spectrum (NdPO4 PDF#25-1065), the peak shape of the spectrum does not change after the introduction of Fe, but the peak diffraction angle shifts significantly, which is consistent with the characteristics of metal element bulk phase composite or solid solution formation, indicating that the sample can be attributed to a single-phase high-entropy 6-membered metal phosphate structure; the morphology is changed from Figure 2 Scanning electron microscope images show that the sample appears to be particles of similar size and uniform distribution, which further proves that the synthesized 6-membered phosphate sample is in a single crystalline phase; for the reaction of anisole, 1 mmol anisole, 50 mg catalyst, 30% H2O2 and 5 ml acetonitrile were charged into a 10 ml double-necked round-bottom flask reactor with a magnetic stirrer, and the molar ratio of H2O2 to anisole was controlled to 2:1. The reaction was carried out at 60°C for 120 min. As shown in Table 1, the yield of sulfoxide was 93%.

[0022] Example 2: In-(LaCeNdSmGd)PO4 Catalyst

[0023] Dissolve 1 mmol of each of In(NO3)3·5H2O and five kinds of rare earth nitrates RE(NO3)3·6H2O (RE=La, Ce, Nd, Sm, Gd) in 30 mL of deionized water, then add 30 mL of 0.2 mol / l diammonium hydrogen phosphate aqueous solution to the above nitrate solution at a rate of 0.5 ml / min under stirring, transfer to a hydrothermal reactor after stirring at 600 r / min for 30 minutes, and perform hydrothermal reaction at 180°C for 24 hours. After the reaction, separate the precipitate by centrifugation, wash it alternately with ethanol and deionized water four times, and vacuum dry it at 60°C for 12 hours to obtain a precursor; the precursor is calcined at 600°C in air for 4 hours to obtain the In-(LaCeNdSmGd)PO4 catalyst sample. As shown in Table 1, the molar ratio of each element in the sample is obtained by ICP-OES analysis: In: La: Ce: Nd: Sm: Gd: P = 0.13: 0.15: 0.17: 0.19: 0.17: 0.14: 1; the XRD spectrum of the sample is shown in Figure 1 , which is similar to the spectrum of Fe-(LaCeNdSmGd)PO4 sample, and can be attributed to a single-phase high-entropy 6-membered metal phosphate structure (NdPO4PDF#25-1065); for the reaction of anisole, 1mmol anisole, 50mg catalyst, 30% H2O2 and 5ml acetonitrile were charged into a 10ml double-necked round-bottom flask reactor with a magnetic stirrer, and the molar ratio of H2O2 to anisole was controlled to be 2:1. The reaction was carried out at 60℃ for 120min. As shown in Table 1, the yield of sulfoxide was 91%.

[0024] In order to further illustrate the characteristics of the sample of the present invention, the following comparative examples are selected:

[0025] Comparative Example 1: (LaCeNdSmGd)PO4 Catalyst

[0026] Dissolve 1 mmol of each of five rare earth nitrates RE(NO3)3·6H2O (RE=La, Ce, Nd, Sm, Gd) in 30 mL of deionized water, then add 30 mL of 0.17 mol / l diammonium hydrogen phosphate aqueous solution to the nitrate solution at a rate of 0.5 ml / min under stirring, transfer to a hydrothermal reactor after stirring at 600 r / min for 30 minutes, and perform hydrothermal reaction at 180°C for 24 hours. After the reaction, separate the precipitate by centrifugation, wash it four times alternately with ethanol and deionized water, and vacuum dry it at 60°C for 12 hours to obtain a precursor; calcine the precursor at 600°C in air for 4 hours to obtain a (LaCeNdSmGd)PO4 catalyst sample. As shown in Table 1, the molar ratio of each element in the sample obtained by ICP-OES analysis is: La:Ce:Nd:Sm:Gd:P=0.18:0.19:0.21:0.20:0.19:1.

[0027] For the reaction of thioanisole, 1 m mol thioanisole, 50 mg catalyst, 30% H2O2 and 5 ml acetonitrile were charged into a 10 ml double-necked round-bottom flask reactor with a magnetic stirrer. The molar ratio of H2O2 to thioanisole was controlled to be 2:1. The reaction was carried out at 60°C for 120 min. As shown in Table 1, the yield of sulfoxide was only 13%.

[0028] Comparative Example 2: Cu-(LaCeNdSmGd)PO4 Catalyst

[0029] Dissolve 1 mmol of each of Cu(NO3)2·2H2O and five kinds of rare earth nitrates RE(NO3)3·6H2O (RE=La, Ce, Nd, Sm, Gd) in 30 mL of deionized water, then add 30 mL of 0.2 mol / 1 diammonium hydrogen phosphate aqueous solution to the above nitrate solution at a rate of 0.5 ml / min under stirring, transfer to a hydrothermal reactor after stirring at 600 r / min for 30 minutes, and perform hydrothermal reaction at 180°C for 24 hours. After the reaction, separate the precipitate by centrifugation, wash it alternately with ethanol and deionized water four times, and vacuum dry it at 60°C for 12 hours to obtain a precursor; calcine the precursor at 600°C in air for 4 hours to obtain a Cu-(LaCeNdSmGd)PO4 catalyst sample. As shown in Table 1, the molar ratio of each element in the sample is obtained by ICP-OES analysis: Cu: La: Ce: Nd: Sm: Gd: P = 0.03: 0.15: 0.17: 0.21: 0.19: 0.18: 1. The molar composition of Cu element is much lower than that of rare earth elements, which does not conform to the composition characteristics of high entropy compounds. The XRD spectrum of the sample is shown in Figure 1 , only the diffraction pattern of the NdPO4 standard spectrum (NdPO4PDF#25-1065) can be analyzed, and the bulk lattice bonding characteristics of the Cu element are not significant; compared with the characteristics of the embodiment, it can be considered that Cu is not combined with the five rare earths to form a 6-membered high-entropy phosphate.

[0030] For the reaction of thioanisole, 1 m mol thioanisole, 50 mg catalyst, 30% H2O2 and 5 ml acetonitrile were charged into a 10 ml double-necked round-bottom flask reactor with a magnetic stirrer. The molar ratio of H2O2 to thioanisole was controlled to be 2:1. The reaction was carried out at 60°C for 120 min. As shown in Table 1, the yield of sulfoxide was only 36%.

[0031] Comparative Example 3: Al-(LaCeNdSmGd)PO4 Catalyst

[0032] 1mmol each of Al(NO3)2·4H2O and 5 kinds of rare earth nitrates RE(NO3)3·6H2O (RE=La, Ce, Nd, Sm, Gd) were dissolved in 30mL of deionized water, and then 30mL of 0.2mol / 1 diammonium hydrogen phosphate aqueous solution was added dropwise to the above nitrate solution at a speed of 0.5ml / min under stirring, and after stirring at 600r / min for 30 minutes, the mixture was transferred to a hydrothermal reactor and hydrothermally reacted at 180℃ for 24h. After the reaction, the precipitate was separated by centrifugation, washed alternately with ethanol and deionized water four times, and vacuum dried at 60℃ for 12h to obtain a precursor; the precursor was calcined at 600℃ in air for 4h to obtain the Al-(LaCeNdSmGd)PO4 catalyst sample. As shown in Table 1, the molar ratio of each element in the sample is obtained by ICP-OES analysis: Al: La: Ce: Nd: Sm: Gd: P = 0.03: 0.17: 0.18: 0.20: 0.19: 0.20: 1. The molar composition of Al element is much lower than that of rare earth elements, which does not conform to the composition characteristics of high entropy compounds. The XRD spectrum of the sample is shown in Figure 1 , only a diffraction pattern similar to the NdPO4 standard spectrum (NdPO4PDF#25-1065) can be analyzed, which does not conform to the element lattice bonding characteristics; compared with the characteristics of the embodiment, it can be considered that Al is not combined with the five rare earths to form a 6-membered high entropy phosphate.

[0033] For the reaction of anisole, 1 m mol anisole, 50 mg catalyst, 30% H2O2 and 5 ml acetonitrile were charged into a 10 ml double-necked round-bottom flask reactor with a magnetic stirrer. The molar ratio of H2O2 to anisole was controlled to be 2:1. The reaction was carried out at 60°C for 120 min. As shown in Table 1, the yield of sulfoxide was 25%.

[0034] Table 1. Composition and performance parameters of the synthesized polyphosphate catalysts

[0035]

[0036] The results in Table 1 show that the single-phase high-entropy 6-membered metal phosphate containing Fe or In as a catalyst applied for in the present invention can efficiently catalyze the oxidation of anisole to prepare sulfoxide products, and the sulfoxide yield is much higher than that of catalysts made of other metal phosphates.

[0037] The above only expresses the preferred embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications, improvements and substitutions can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A method for preparing a single-phase high-entropy rare earth-based ceramic catalyst containing Fe or In, characterized in that: The preparation method comprises the following steps: uniformly mixing nitrate M(NO3)3 and five kinds of rare earth nitrates RE(NO3)3 in an aqueous solution, wherein M=Fe or In, and RE=La, Ce, Nd, Sm and Gd; adding an excess of phosphorus-containing ligands for hydrothermal synthesis reaction; and calcining the obtained composite sediment to obtain a 6-element metal phosphate ceramic material, i.e., a single-phase high-entropy rare earth-based ceramic catalyst containing Fe or In.

2. The method for preparing a single-phase high-entropy rare earth-based ceramic catalyst containing Fe or In according to claim 1, characterized in that: The preparation method specifically comprises the following steps: (1) Iron nitrate (Fe(NO3)3) or indium nitrate (In(NO3)3) is mixed with five kinds of rare earth nitrates in a certain molar ratio to prepare an aqueous solution, an excess of phosphorus-containing ligand is added, and after stirring at 500-700 r / min for 20-40 minutes, the mixture is transferred to a hydrothermal reactor and reacted at 150-200 °C for 20-30 hours; (2) The precipitate obtained by centrifuging the reaction solution system is washed alternately four times with ethanol and deionized water, and then vacuum dried at 50-70°C for 10-14 h to obtain a precursor; (3) The precursor is calcined in air at 500-700 °C for 3-5 h to obtain a hexavalent metal phosphate catalyst.

3. The method for preparing a single-phase high-entropy rare earth-based ceramic catalyst containing Fe or In according to claim 1 or 2, characterized in that: The phosphorus-containing ligand refers to phosphoric acid or phosphate, and the excess means that the molar ratio of the phosphorus-containing ligand to the total amount of the metal element is controlled to be 1.1-1.

5.

4. The method for preparing a single-phase high-entropy rare earth-based ceramic catalyst containing Fe or In according to claim 2, characterized in that: Taking the molar composition of phosphate in the phosphorus-containing ligand as unit 1, the molar ratio is La:Ce:Nd:Sm:Gd:M:P =0.16± 0.04:0.16± 0.04:0.16± 0.04:0.16± 0.04:0.16± 0.04:0.16± 0.04:0.16± 0.04:

1.

5. A single-phase high-entropy rare earth-based ceramic material containing Fe or In prepared by the method according to any one of claims 1 to 4.

6. The single-phase high-entropy rare earth-based ceramic material containing Fe or In according to claim 5, characterized in that: The single-phase high-entropy rare earth-based ceramic material containing Fe or In is a hexavalent metal phosphate in a single crystal phase.

7. Application of a single-phase high-entropy rare earth-based ceramic material containing Fe or In prepared by the method according to any one of claims 1 to 4, characterized in that: The single-phase high-entropy rare earth-based ceramic material containing Fe or In is used as a catalyst for the thermal catalytic reaction of oxidizing anisyl thioether to prepare sulfoxide compounds.

8. The use according to claim 7, characterized in that: The method for oxidizing anisole to prepare sulfoxide compounds comprises: dissolving anisole in an acetonitrile solution, adding the Fe or In-containing single-phase high-entropy rare earth-based ceramic material as a catalyst, and then adding H2O2 solution, heating the reaction, and generating sulfoxide compounds.

9. The use according to claim 8, characterized in that: The molar ratio of H2O2 to thioanisole is 1.5~2.5:1, the reaction temperature is 50~70 ℃, and the reaction time is 120~150 min.

Citation Information

Patent Citations

  • Metal phosphates and process for the preparation thereof

    CN103946156A

  • High-entropy rare-earth phosphate powder and preparation method thereof

    CN110386595A